EFFECTS OF SEASON AND DIURNAL PERIOD ON THE BODY PHYSIOLOGY OF NIGERIAN SHEEP BREEDS - UMESIOBI, D. O. (Nigerian Journal of Animal Science, 2023)
Eight 2-year-old adult ewes each belonging to Balami, Ouda, WAD and Balami X WAD were used in an experiment to determine the effects of dry and rainy seasons, and diurnal (morning and afternoon) period on the rectal temperature (R?']. Pulse rate (PR) and respiration rate (RR) of Nigerian sheep breeds. The highest climatic values were recorded mostly during the dry season, in the afternoon hour from: ambient temperature (31.56OC1, radiation intensity (1.14K~alcm-~), maximum temperature (31, 87"C), minimum temperature (21.87"C), dry bulb temperature (31.87°C), wet bulb temperature (23.27'C) and wind velocity (11.33knlhr2). However, the relative humidity had the highest (84.0%) value during the rainy season, in the morning hours. Most of the climatic variables were positively correlated to ambient temperature, except the relative hunjiditji which had negative correlation (-0.08) with ambient temperature. The results obtained suggested that season and diurnal period produced significant (P<0.05) influences on RT, PR and RR, mostly in Balami and Buda, with the highest physio Biological values obtained during the dry season, in the afternoon hours. Balami WAD produced the narrowest RT (38.13-38.60°C), and lowest PR (78.07 breaths/min.) and RR (33.22 breaths/min.). WAD ranked second in producing low PR (75.44 breaths/min.) and RR (37.46 breaths/min.). On the contrary, season and diurnal period elevated the physiological parameters especially the PR (78.02 and 81.54 breaths/min.) and RR (58.72 and 58.80 breath/min.) of Balami and Oud a respectively. This study suggests that Balami X WAD followed by WAD are the Nigerian sheep breeds better adapted to the humid tropical climate,